A composite material with specific selectivity for triethylamine in mixed gas, its preparation method and application in environmental detection

CN116297708BActive Publication Date: 2026-10-27GUANGZHOU ZHONGKE TESTING TECH SERVICE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310229782.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-10
Publication Date
2026-10-27
Estimated Expiration
2043-03-10

AI Technical Summary

Technical Problem

[0005]目前尚未见有MXene/Co9S8/In2S3的纳米复合的三乙胺选择性材料

Benefits of technology

[0024](1)本发明的MXene/Co9S8/In2S3传感器件可实现对混合气中的三乙胺进行特异选择性,提升了传感数据的可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004119878990000081
    Figure BDA0004119878990000081
  • Figure BDA0004119878990000091
    Figure BDA0004119878990000091
  • Figure HDA0004119879000000011
    Figure HDA0004119879000000011
Patent Text Reader

Abstract

The application belongs to the technical field of compound semiconductor functional materials and chemical sensors, and discloses a composite material with specific selectivity to triethylamine in a mixed gas, a preparation method of the composite material, and application of the composite material in environmental detection. x The MXene material of Ti3C2T x type is compounded with Co9S8 / In2S3 to construct a MXene / Co9S8 / In2S3 type triethylamine specific selection response nanocomposite material, the specific selection response of the nanocomposite material to triethylamine has excellent specificity and sensitivity, adsorption and desorption are stable, the response sensitivity is far more than about 40 times of that to other gases, the response / recovery time at 350 DEG C is 62s / 112s, compared with the pure Co9S8 / In2S3 material, the total adsorption / desorption time is reduced by about 300s, and the response speed is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of compound semiconductor functional materials and chemical sensor technology, and specifically relates to a composite material with specific selectivity for triethylamine in a gas mixture, its preparation method, and its application in environmental monitoring. Background Technology

[0002] Triethylamine (TEA) is widely used in the chemical industry. International occupational safety and health technical standards stipulate an air concentration limit of 10 ppm and a workplace occupational exposure limit—time-weighted average permissible concentration (PC-TWA) of 1 ppm. Among the known triethylamine selective response materials and sensor technologies, there are problems such as high response concentrations and selectivity and stability being easily affected by other factors.

[0003] For example, in patent application CN202111330144.X, the structural advantages and high catalytic activity of the hierarchical microsphere sensitive material assembled from low-coordination Co3O4 mesoporous nanosheets were utilized to effectively improve the detection range (0.5–100 ppm) and sensitivity (34.1–100 ppm) for a single triethylamine gas. However, because this method also exhibits some response to gases such as ethanol and acetone, a significant bias occurs when it is used to detect triethylamine mixtures containing ethanol, acetone, etc. Gui Yanghai et al. constructed WO3 nanosheets using in-situ reaction and then modified the surface with ZIF-67 to obtain a ZIF-67 / WO3 (1:1) composite material. This achieved a good response to 100 ppm triethylamine at 220℃, with response / recovery times of 9 s and 7 s, respectively. It also exhibited good stability in a high-humidity environment of 75% RH. However, this material also showed non-negligible responsiveness to ammonia, isopropanol, hydrogen sulfide, and nitrogen, which inevitably led to biases in monitoring data when faced with triethylamine mixtures containing these gases. The above work determined the selective responsiveness of gas-sensitive materials by analyzing the differences in their responsiveness to single gases, a commonly used method. However, in practical applications, the effective selective monitoring of a single gas in a gas mixture is often required. To achieve stable selective responsiveness to specific gases in a gas mixture, corresponding material development is needed to truly realize highly stable and specific selectivity in gas-responsive functional materials.

[0004] Among them, the two-dimensional crystal Ti3C2Tx MXene has a very high aspect ratio and a very thin electronic layer. Due to its rich chemical composition and unique morphology, it has good electronic conductivity and has become a popular candidate material in the field of sensors. In2S3 is an n-type sulfide semiconductor with a band gap of 2-3 eV, and it has mature applications in optoelectronic devices. The metal-organic framework Zif-67 is a dodecahedral structure with high porosity and is often used as a precursor and self-sacrificing template for nanosynthesis, which is very beneficial for the preparation of stable selective response materials. At the same time, the nanoflower structure prepared by Xue Dongping et al. has a special configuration that increases the specific surface area of ​​the semiconductor material, providing a reference for the preparation of materials in this study. Wang Ke et al. reported a method for preparing the sulfide heterojunction Co9S8@In2S3, which was applied to the field of photocatalysis, providing a reference for the preparation of heterojunctions between cobalt and indium sulfides.

[0005] Currently, there are no known triethylamine-selective materials composed of MXene / Co9S8 / In2S3 nanocomposites. Summary of the Invention

[0006] In order to overcome the shortcomings and deficiencies of the existing technology, the primary objective of this invention is to provide a method for preparing a composite material with specific selectivity for triethylamine in a gas mixture.

[0007] Another objective of this invention is to provide a composite material prepared by the above-mentioned preparation method. This is an MXene / Co9S8 / In2S3 nanocomposite material that can achieve a specific selective response to triethylamine in a mixed gas. It has the advantage of specific selective response to triethylamine in a mixed gas, which can effectively avoid the competition, interference and reduction effects that may exist between the components of the mixed gas during the response process. It better ensures the specificity and response intensity of the selective response to triethylamine, and effectively ensures the reliability of the acquired monitoring data.

[0008] Another object of the present invention is to provide the application of the above-mentioned composite material in environmental testing.

[0009] The objective of this invention is achieved through the following technical solution:

[0010] A method for preparing a composite material with specific selectivity for triethylamine in a gas mixture includes the following steps: reacting a Co9S8 / In2S3 mixture obtained using a ZIF-67 precursor with 0.5–2.5 mg / mL Ti3C2T x A hydrothermal reaction was carried out with an aqueous solution of MXene to obtain a composite material with specific selectivity for triethylamine in the mixed gas.

[0011] The above preparation method specifically follows these steps: Ti3C2T x Ti3C2T was obtained by ultrasonically dispersing MXene powder in deionized water. x MXene aqueous solution; ZIF-67 precursor, thioacetamide, and indium nitrate hydrate were ultrasonically dissolved in ethanol, and then reacted with the above-mentioned Ti3C2T x After mixing the MXene aqueous solution, the mixture was stirred for 5–60 minutes, followed by a hydrothermal reaction. After the reaction was completed, the mixture was allowed to cool naturally, and the precipitate was collected by centrifugation. The precipitate was then washed with ethanol and deionized water and dried at 30–120°C for 5–30 hours to obtain the MXene / Co9S8 / In2S3 nanocomposite material, which is a composite material with specific selectivity for triethylamine in the mixed gas.

[0012] The mass ratio of the ZIF-67 precursor, indium nitrate hydrate, and thioacetamide is 1:1:(1.2–2.4).

[0013] The thioacetamide and Ti3C2T x The mass ratio of type MXene powder is 15:(1~5);

[0014] The Ti3C2T x The concentrations of the MXene aqueous solution are 0.5 mg / mL, 1.0 mg / mL, 1.5 mg / mL, 2.0 mg / mL, or 2.5 mg / mL;

[0015] The stirring speed is 60 rpm to 1000 rpm, and the stirring time is 10 to 30 minutes;

[0016] The drying process involves drying at 60°C for 10 hours.

[0017] The Ti3C2T x Ti3AlC2 type MXene powder was prepared by the following method: LiF and Ti3AlC2 type MXene powder were mixed, and 50 ml of concentrated hydrochloric acid was added under uniform stirring. The mixture was reacted at room temperature for 24 h until the supernatant was light green or green. The precipitate was separated by centrifugation and washed repeatedly with deionized water until the pH of the supernatant was ≈7. The obtained solid powder was dried at 60 °C for 10 h to obtain a monolayer or at least layered Ti3C2T x Type MXene powder.

[0018] The hydrothermal reaction is carried out at 120–180°C for 3–12 hours, preferably at 155–165°C for 5.5–7.5 hours, and more preferably at 160°C for 6 hours.

[0019] The ZIF-67 precursor is obtained by dissolving cobalt nitrate hexahydrate and dimethylimidazole in methanol at a molar ratio of 1:2 to 8, reacting with ultrasonic power at 240 to 600 W, allowing it to stand at room temperature for no less than 48 hours, and then collecting the precipitate by centrifugation.

[0020] A composite material prepared by the above preparation method, which exhibits specific selectivity for triethylamine in a mixed gas, wherein the composite material contains loosely packed microspheres and nanoflower structures attached to the MXene sheets.

[0021] The above-mentioned composite material with specific selectivity for triethylamine in gas mixtures is used in sensor devices.

[0022] The sensor is a triethylamine selective responsive sensor, exhibiting excellent triethylamine selective response characteristics in mixed gases.

[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0024] (1) The MXene / Co9S8 / In2S3 sensor of the present invention can achieve specific selectivity for triethylamine in the gas mixture, thereby improving the reliability of the sensing data.

[0025] (2) The response recovery time of the MXene / Co9S8 / In2S3 sensor device of the present invention is 112s, which is about 300s shorter than the response recovery time of the sensor device without MXene modification.

[0026] (3) The response recovery curve of the MXene / Co9S8 / In2S3 sensor of the present invention is very stable, more stable than the adsorption-desorption curve of the material without MXene modification, and has no impurity peaks, which can more effectively resist environmental interference.

[0027] (4) The composite material of the present invention, which has specific selectivity for triethylamine in the mixed gas, has significant triethylamine selective response characteristics. It has excellent specificity and sensitivity in the selective response to triethylamine and stable adsorption and desorption. Taking a triethylamine concentration of 20 ppm as an example, the selective response of the MXene / Co9S8 / In2S3 heterojunction gas sensing device of the present invention to triethylamine is about 40 times that of other gases (triethylamine, ammonia, ethanol, ethylamine, toluene, diethylamine, acetone, methanol, formaldehyde, xylene). The response / recovery time at 350℃ is 62s / 112s. Compared with the pure Co9S8 / In2S3 material, the total adsorption / desorption time is reduced by about 300s, and the response speed is significantly improved.

[0028] (5) The composite material of the present invention, which has specific selectivity for triethylamine in mixed gas, has good adaptability to environmental humidity. In the humidity range of 40-70%RH, the response value of the MXene / Co9S8 / In2S3 sensor can be stably maintained above 16 at 10ppm; it can meet the requirements of triethylamine detection in daily chemical plants and scientific research.

[0029] (6) The MXene / Co9S8 / In2S3 nanocomposite material and device prepared in this invention have the advantage of specific selective response to triethylamine in mixed gas. This effectively avoids possible interference, competition, and attenuation effects between the components of the mixed gas during the response process, ensuring the specificity and intensity of the selective response to triethylamine, and effectively guaranteeing the reliability of monitoring data obtained in simulated real-world environments. It has broad technical and market prospects in the real-time detection of triethylamine. Attached Figure Description

[0030] Figure 1 This is a SEM image of the composite material obtained in Example 1 of the present invention.

[0031] Figure 2 This is a diagram showing the average time of the desorption process of the composite materials obtained in Examples 1-5 of the present invention.

[0032] Figure 3 The graph shows the stable response recovery of the composite materials obtained in Example 1 and Comparative Example 1 of this invention to 20 ppm triethylamine at an operating temperature of 350°C.

[0033] Figure 4 This is a comparison chart of the selective response of the composite material obtained in Example 1 of the present invention to a single gas.

[0034] Figure 5 This is a comparison diagram of the selective response of the composite material obtained in Example 1 of the present invention to the mixed gas.

[0035] Figure 6 The sensitivity of the composite material obtained in Example 1 of the present invention to 1-100 ppm triethylamine gas is shown. Detailed Implementation

[0036] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto.

[0037] Example 1

[0038] An MXene / Co9S8 / In2S3 composite material exhibiting specific selectivity for triethylamine in a mixed gas is prepared according to the following steps:

[0039] (1)Ti3C2T xType MXene: 4.0 g of lithium fluoride (LiF) and 2.5 g of Ti3AlC2 type MXene powder were mixed evenly in a polytetrafluoroethylene (PTFE) beaker. A magnetic stirrer was turned on, and the PTFE stir bar was rotated. 50 ml of 9 mol / L concentrated hydrochloric acid (HCl) was slowly added. The reaction was carried out at room temperature for 24 h until the supernatant was pale green or green. The precipitate was collected by centrifugation and washed with deionized water. Multiple centrifugation and washing with water were performed. The pH of the supernatant after the last wash was close to 7. The mixture was dried at 60 °C for 10 h to obtain monolayer / few-layer Ti3C2T. x Type MXene.

[0040] (2) Preparation of ZIF-67 precursor: 2.95g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) was dissolved in 100mL of methanol solution, which was denoted as solution A; 3.28g of dimethylimidazole was dissolved in 100mL of methanol solution, which was denoted as solution B; under ultrasonic conditions, solution A was slowly introduced into solution B, and the ultrasonic treatment was turned off after half an hour. After the ultrasonic reaction, the mixture was allowed to stand at room temperature for no less than 48h. The precipitate was collected by centrifugation to obtain the precursor ZIF-67, which was washed with methanol and dried at 60℃ for 10h to obtain the ZIF-67 precursor.

[0041] (3) Preparation of MXene / Co9S8 / In2S3: 90 mg of ZIF-67 precursor, 150 mg of thioacetamide, and 90 mg of indium nitrate hydrate were ultrasonically dissolved in 30 mL of ethanol. 20 mg of the Ti3C2T obtained in step (1) was added... x MXene was ultrasonically dispersed in 20 mL of deionized water to obtain Ti3C2T with a concentration of 1.0 mg / mL. x A dispersion of type MXene; then Ti3C2T x A dispersion of type MXene was mixed with a solution of 90 mg ZIF-67 precursor, 150 mg thioacetamide, and 90 mg indium nitrate hydrate dissolved in 30 mL of ethanol via ultrasonication. After stirring at 500 rpm for 20 minutes, the mixture was placed in a reactor and reacted at 160 °C for 6 hours. After natural cooling, the precipitate was collected by centrifugation, washed with ethanol and deionized water, and dried at 60 °C for 10 hours to obtain an MXene / Co9S8 / In2S3 composite material with specific selectivity for triethylamine in the mixed gas.

[0042] Performance testing:

[0043] (1) The SEM morphology images of the MXene / Co9S8 / In2S3 composite material with specific selectivity for triethylamine in the mixed gas prepared in this embodiment are as follows: Figure 1 As shown. From Figure 1It can be seen that the MXene / Co9S8 / In2S3 nanocomposite material consists of many small nanoparticles adhered to a layered structure, in which the surface of the layered structure becomes rough. Figure 1 Nanoflowers appear in the lower right corner, exhibiting both microspheres attached to the MXene structure and nanoparticles self-assembling into nanoflower structures at the microscopic level. This unique structure retains the characteristics of MXene while leveraging the advantages of the Co9S8 / In2S3 heterojunction structure. The two are arranged in a specific ratio, working synergistically. The presence of both the MXene conductive framework and the nanoflower structure ensures high sensitivity. Macroscopically, this manifests as an increase in the material's specific surface area, increasing the contact area between the material and the gas, while the MXene framework provides sensing stability and interference resistance.

[0044] (2) The sensitivity and response-recovery time of the MXene / Co9S8 / In2S3 composite material with specific selectivity for triethylamine in the mixed gas prepared in this embodiment were determined at 350℃ for 20 ppm triethylamine gas using a CGS-8 intelligent gas-sensitive analysis system (Beijing Elite Technology Co., Ltd., model CGS-8). The stability of the material was examined by measuring the sensitivity values ​​and response-recovery times through multiple tests. The gas response sensitivity was calculated using the formula: S = Ra / Rg, where Rg is the resistance of the sensor in the target gas; Ra is the resistance of the sensor in air. The response-recovery time can also be obtained by instrument testing.

[0045] Figure 2 At 350°C, the desorption time of the MXene / Co9S8 / In2S3 composite materials obtained in Examples 1-5 gradually shortened with increasing MXene content, indicating that the introduction of MXene increases its specific surface area and provides a layered MXene framework to enhance its stability. Based on this pattern, sensitivity tests were conducted at MXene content ranging from 10% to 50%. At an MXene content of 20%, the overall performance of the triethylamine response was excellent, as shown in Example 1. Figure 3 As a comparative example, the Co9S8 / In2S3 composite material and the MXene / Co9S8 / In2S3 composite material obtained at 350℃ showed a sensitivity of 43.1 to the response of 20ppm and a desorption time of 112s, which was 300s less than the desorption time of the unmodified material. Moreover, the adsorption and desorption processes were not affected by many environmental factors that caused impurity peaks, indicating that the MXene-modified material has good comprehensive performance. Figure 4The values ​​represent the response of the MXene / Co9S8 / In2S3 composite material to various gases at 20 ppm at 350 °C, including trimethylamine, ammonia, ethanol, ethylamine, toluene, diethylamine, acetone, methanol, formaldehyde, and xylene. The response to triethylamine is approximately 35–40 times greater than that to the other gases, demonstrating excellent selectivity. Figure 5 This is a laboratory simulation application scenario. Under three gas mixtures, it still maintains high selectivity for triethylamine. Triethylamine's ability to compete for adsorption sites is higher than that of other gases, ensuring the specificity and intensity of the triethylamine selective response in practical applications. The first gas mixture consists of 10 ppm triethylamine, 10 ppm ammonia, and 10 ppm diethylamine; the second gas mixture consists of 10 ppm triethylamine, 10 ppm acetone, 10 ppm methanol, and 10 ppm ethanol; and the third gas mixture consists of 10 ppm triethylamine, 10 ppm toluene, and 10 ppm xylene. Figure 6 The results show the response of the MXene / Co9S8 / In2S3 composite material to different concentrations of triethylamine. The detection limit is 1 ppm, and the adsorption basically follows a linear law in the range of 1 ppm to 20 ppm. The adsorption is in the near-saturation and adsorption saturation states in the range of 50 to 200 ppm.

[0046] Examples 2-5

[0047] In Examples 2-5, the preparation and performance testing processes are basically similar to those in Example 1, except for the material ratios in Table 1 below.

[0048] Comparative Example 1

[0049] A method for preparing Co9S8 / In2S3 nanocomposite materials includes the following steps:

[0050] ZIF-67 is consistent with the embodiment.

[0051] 90 mg of ZIF-67 precursor, 150 mg of thioacetamide, and 90 mg of indium nitrate hydrate were ultrasonically dissolved in 30 mL of ethanol and placed in a reaction vessel to react at 160 °C for 6 hours. After natural cooling, the precipitate was collected by centrifugation, washed with ethanol and deionized water, and then dried at 60 °C for 10 hours to obtain Co9S8 / In2S3 nanocomposite material.

[0052] Comparative Example 2

[0053] A method for preparing a comparative sample of MXene includes the following steps:

[0054] 20mg of Ti3C2T x MXene was ultrasonically dispersed in 20 mL of deionized water to obtain Ti3C2T with a concentration of 1.0 mg / mL. xThe MXene dispersion was prepared by adding 30 mL of ethanol and stirring at high speed for 20 minutes, then reacting in a reactor at 160°C for 6 hours. After natural cooling, the precipitate was collected by centrifugation, washed with ethanol and deionized water, and dried at 60°C for 10 hours to obtain MXene.

[0055] For ease of comparison, the preparation processes of Examples 1-5 and Comparative Examples 1-2, as well as their corresponding response characteristics, are listed in Table 1 below.

[0056] Table 1 Comparison of the selective response characteristics of MXene / Co9S8 / In2S3 composite materials to triethylamine in gas mixtures

[0057]

[0058]

[0059] As can be seen from Table 1, the sensitivity of Example 1 prepared by the present invention to 20 ppm triethylamine is 40.3, which is greater than the sensitivity of the other examples in the table. The sum of the response time and recovery time is less than that of Comparative Example 1. In other words, Example 1 prepared by the present invention has excellent comprehensive performance and is suitable for widespread application.

[0060] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for preparing a composite material with specific selectivity for triethylamine in a gas mixture, characterized in that... The specific steps are as follows: Place the Ti3C2T... x MXene powder was ultrasonically dispersed in deionized water to obtain 0.5~2.5 mg / mL Ti3C2T x MXene aqueous solution; ZIF-67 precursor, thioacetamide, and indium nitrate hydrate were ultrasonically dissolved in ethanol, and then reacted with the above-mentioned Ti3C2T x After mixing the MXene aqueous solution, the mixture was stirred for 5-60 minutes, followed by a hydrothermal reaction. After the reaction was completed, the mixture was naturally cooled, centrifuged to collect the precipitate, washed with ethanol and deionized water, and dried at 30℃-120℃ for 5-30 hours to obtain the MXene / Co9S8 / In2S3 nanocomposite material, which is a composite material with specific selectivity for triethylamine in the mixed gas.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the ZIF-67 precursor, indium nitrate hydrate, and thioacetamide is 1:1:(1.2-2.4). The thioacetamide and Ti3C2T x The mass ratio of type MXene powder is 15:(1-5); The Ti3C2T x The concentrations of the aqueous solution of type MXene are 0.5 mg / mL, 1.0 mg / mL, 1.5 mg / mL, 2.0 mg / mL, or 2.5 mg / mL; The stirring speed is 60 rpm to 1000 rpm, and the stirring time is 20 minutes; The drying process involves drying at 60°C for 10 hours.

3. The preparation method according to claim 1, characterized in that: The Ti3C2T x Ti3AlC2 type MXene powder was prepared by the following method: LiF and Ti3AlC2 type MXene powder were mixed, and 50 ml of concentrated hydrochloric acid was added under uniform stirring. The mixture was reacted at room temperature for 24 h until the supernatant was light green or green. The precipitate was separated by centrifugation and washed repeatedly with deionized water until the pH of the supernatant was ≈7. The obtained solid powder was dried at 60 °C for 10 h to obtain monolayer or at least layered Ti3C2T x Type MXene powder.

4. The preparation method according to claim 1, characterized in that: The hydrothermal reaction is carried out at 120~180℃ for 3~12 hours.

5. The preparation method according to claim 1, characterized in that: The hydrothermal reaction is carried out at 155–165°C for 5.5–7.5 hours.

6. The preparation method according to claim 1, characterized in that: The ZIF-67 precursor is obtained by placing cobalt nitrate hexahydrate and dimethylimidazole in methanol at a molar ratio of 1:2 to 8, reacting with ultrasonic power at 240 to 600 W, allowing it to stand at room temperature for no less than 48 hours, and then collecting the precipitate by centrifugation.

7. A composite material with specific selectivity for triethylamine in a gas mixture, prepared by the method of claim 1, characterized in that: The composite material contains a nanostructure of loosely packed microspheres and a nanoflower structure attached to the MXene lamellars.

8. The application of the composite material with specific selectivity for triethylamine in a gas mixture as described in claim 7 in sensor devices.

9. The application according to claim 8, characterized in that: The sensor is a triethylamine selective responsive sensor, exhibiting excellent triethylamine selective response characteristics in mixed gases.

Citation Information

Patent Citations

  • Triethylamine Gas Sensor Based on Hierarchical Microsphere Sensing Material Assembled from Low-Coagulation Co3O4 Mesoporous Nanosheets and Its Preparation Method

    CN114062444B

  • Material with stable selection response to triethylamine, preparation method of material and sensing device with triethylamine selection response

    CN114113239A